KETERKAITAN JUMLAH DAERAH TERMUTASI PADA GEN β-GLOBIN DENGAN INDEKS KORPUSKULAR PEMBAWA SIFAT β-THALASSEMIA - Priyambodo, Priyambodo (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2016)
Thalassemia is a genetic disorder caused by point mutations on the globin gene that decrease the corpuscular index in thalassemia carriers. Three to five percent of Indonesians are thalassemia carriers, with β-thalassemia being the most common type. This research aimed to identify the relationship between the number of mutated regions on the β-globin gene and the decrease in corpuscular index among β-thalassemia carriers. Data was collected from 2012 to 2013 in Yogyakarta. Hematological analysis was performed by assessing the corpuscular index, including mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC) at Prodia Laboratory. Molecular analysis was conducted using the polymerase chain reaction-single strand conformation polymorphism (PCR-SSCP) method at the Laboratory of Genetics and Laboratory of Falitma, Biology Faculty, University of Gadjah Mada. Out of a total of 96 individuals screened, there were 9 suspected β-thalassemia carriers with 1 mutated region of the β-globin gene, showing an average MCV of 63.1 fl, MCH of 19.76 pg, and MCHC of 32.34 g/dl. Seven suspected β-thalassemia carriers with 2 mutated regions showed an average MCV of 61.16 fl, MCH of 19.74 pg, and MCHC of 32.3 g/dl. One suspected β-thalassemia carrier with 3 mutated regions showed an average MCV of 64.2 fl, MCH of 19.5 pg, and MCHC of 30.4 g/dl. The number of mutated regions in the β-globin gene was not the main factor affecting the decrease in corpuscular index among β-thalassemia carriers.